2016
DOI: 10.1016/j.amc.2015.11.073
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic approach to solve the preventive health care problem with budget and congestion constraints

Abstract: This document is the Accepted Manuscript version of the following article: Soheil Davari, Kemal Kilic, and Siamak Naderi, ???A heuristic approach to solve the preventive health care problem with budget and congestion constraints???, Applied Mathematics and Computation, Vol. 276, pp. 442-453, March 2016. ?? 2016. Under embargo. Embargo end date: 14 January 2018. The Version of Record is available online at doi: https://doi.org/10.1016/j.amc.2015.11.073.Preventive health care is of utmost importance to governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In fact, there are two sources of inaccessible demand: one is demand lost due to insufficient coverage and the other is demand lost due to congested facility (Abouee-Mehrizi et al, 2011;. For the first source, demand is elastic with respect to cost and customers are usually assigned to the closest facilities to maximize system total demand (Berman and Drezner, 2006;Davari et al, 2016;Marianov, 2003;Zhang et al, 2010). For the second source, customers could be denied to access the service (i.e., occurrence of balking) upon their arrival, due to capable space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there are two sources of inaccessible demand: one is demand lost due to insufficient coverage and the other is demand lost due to congested facility (Abouee-Mehrizi et al, 2011;. For the first source, demand is elastic with respect to cost and customers are usually assigned to the closest facilities to maximize system total demand (Berman and Drezner, 2006;Davari et al, 2016;Marianov, 2003;Zhang et al, 2010). For the second source, customers could be denied to access the service (i.e., occurrence of balking) upon their arrival, due to capable space.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2009) further incorporated congestion effect at a facility where the users are assumed to visit the facility with minimum total cost including travel time and queueing time. The queueing time can also be incorporated as a constraint (Davari et al, 2016). Multi-objective location problems are also proposed recently where multiple performances are evaluated (Dogan et al, 2020;Erdoğan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2009) proposed a healthcare facility location model incorporating congestion. Davari et al (2016) suggested a mixed-integer programming model to design a health care network under budget and congestion considerations and also proposed a heuristic approach for solving the proposed model. A congested facility is unable to provide health care services to every patient and the patients are compelled to go elsewhere to get the services.…”
Section: Introductionmentioning
confidence: 99%
“…In another work, Davari et al (2016) presented a mixed-integer programming model for designing preventive healthcare networks subject to budget constraints and equity considerations. They developed a skewed variable neighborhood search algorithm to solve their proposed model.…”
Section: Patient Choice Modelsmentioning
confidence: 99%
“…Preventive services and programs are proven to be contributing to better life quality of patients by reducing the likelihood of receiving radical treatments such as surgery or chemotherapy, as well as saving their lives (Zhang et al 2020). Previous studies showed that even a small amount of improvement in the participation of these services can save massive amounts of money for healthcare organizations and governments (Davari et al 2016). Preventive healthcare is considered the most effective and efficient way of preventing disease and increasing public health in both developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%